PENINGKATAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP ADABIAH PADANG MELALUI PENERAPAN STRATEGI PEMBELAJARAN AKIF TIPE THE POWER OF TWO - Suci Halizarmi (Jurnal Edukasi dan Penelitian Matematika, 2018)
One of the many goals of learning mathematics in school is to make students understand the ability of understanding mathematical concepts. In fact in grade VIII SMP Adabiah Padang, students are still low in understanding and applying this ability. Learning strategies used so that students can understand the concept well with the active learning strategy type of the power of two. The use of strategy is expected to help the students to understand the concept better. Therefore,conducted research in grade VIII SMP Adabiah Padang. The result of the study showed an increase in the ability to understand the mathematical concepts of students after learning to use this strategy in the learning processKeywords – Mathematical Concept, The Power Of Two, Conventional Learning